Adoption Status of Improved Crop Production Practices in Bt-cotton in Sri Muktsar Sahib, Punjab - Sharma, Karamjit; Dhaliwal, N S; Bishnoi, Chetak (Indian Journal of Extension Education, 2021)
The study was conducted to investigate the adoption status of crop production practices in Bt cotton in Sri Muktsar Sahib District of Punjab. The data were collected from 140 growers through personal interviews during 2016-17 and 2017-18. The area under Bt-cotton increased by 10.9% in 2017-18, compared with 2016-17. 80% of farmers ensured cotton sowing in the recommended time period, with the use of 900-1100 g/acre seed rate. This survey showed that farmers did not prefer soaking of seed and refugia in the study region. Nearly 65% of farmers were applying fertilizer-N as per recommended rate, while 30 per cent farmers were applying fertilizer-P as per recommendation. These (57% of total farmers) farmers wereÂ applying 5 irrigations to cotton, while 7 irrigations were applied by only those farmers who had very light textured soils. A great majority of farmers ( 83%) were using manual method for weed control in Bt-cotton,Â and 44.0 per cent were using 3-5 sprays for management of sucking pests. The seed cotton yield of Bt-cottonÂ prominent hybrids varied from 17.5- 23.5 q ha-1, with a mean 19.4 q ha-1.Results highlight the need of intensified extension efforts to disseminate the technology for efficient nutrient, water, and insect-pest management.